A Review of Websites and Mobile Applications for People with Autism Spectrum Disorders: Towards Shared Guidelines - Dattolo, Antonina; Luccio, Flaminia L. (Smart Objects and Technologies for Social Good, 2017)
Many studies show the effective positive impact of using computer technologies to support the lives of users with autism spectrum disorders (ASD), for simplifying interaction with other people, for organising daily activities, for improving relation with family and friends. Despite that, only a restricted part of the current websites is accessible for people with ASD. In this paper, we discuss a set of guidelines that should be followed by designers while developing websites or mobile applications for users with ASD. We review many of the existing websites and applications in order to check which comply with all, or parts of these guidelines. We finally highlight current common limitations and address new challenging research directions.